INTERNAL RESOURCES AS AN ELEMENT OF DEVELOPMENT OF REGIONAL ECONOMY - E. A. Ostapenko (Publishing House of the State University of Management, 2020)
It is impossible to achieve stable growth indicators for various sectors of the economy without the use of microfinance and investment costs in systemically important infrastructure projects, since it is investment processes that affect all levels of regional management. The problems of implementing the mechanism of investment support for the development of domestic resources of the region's economy have been examined in the article; the ways to improve it using the transformation of economic relations between business entities have been proposed. The results of the research can be applied to solve problems associated with the process of reproduction of domestic resources at the regional level, in the development and implementation of investment projects in this direction, as well as in forming the strategy for socio-economic development of the region.